The Determinants of Regional Income Inequality in Russia : A Quantitative Study - Khazieva, Amaliia; Zeynalov, Ayaz; Proch, Dominik; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
Addressing regional income inequality is crucial for sustainable economic development, particularly in a vast and resource-rich country like Russia with notable income disparities. This thesis tests two hypotheses: firstly, that regions with initially lower income per capita may catch up economically with higher-income regions, reducing income disparities; and secondly, that higher average income per capita does not necessarily equate to more equitable income distribution as measured by the Gini coefficient. The methodology involves a comprehensive analysis of regional data from 2008 to 2022, focusing on nominal income per capita, the cost of a fixed basket, and the Gini coefficient, employing Beta convergence models. The results indicate a general trend of income beta convergence across most Russian regions, supporting the first hypothesis of income catch-up, but also reveal significant regional variations in the relationship between average income and income distribution, challenging the second hypothesis and highlighting the complex nature of income inequality in Russia.
Vedoucí práce: Ayaz Zeynalov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses